(untitled) (Global Journal of Human-Social Science, 2012)
This paper presents a literature review of liberal feminist Marxist feminist radical feminist socialist feminist all the other i e lesbian feminist ecofeminist race and ethnicity based feminist and Third World feminist and postmodern feminist accounts of the state Keeping in mind the fact that feminism as listed under the contemporary Western critical paradigm carries the potential to transform the state the paper ends with a brief overview of the possible inheritances of the above mentioned feminisms Choosing to use gender inequality rather than patriarchy as an all-encompassing phrase the paper concludes that in order to develop a common sense on the relationship between the state s the market and the civil society finding historical data that are not contaminated by malestream knowledge remains at the top of the agenda of the feminist political struggle